A Parallel Shallow Water Finite Element Solver for the Venice Lagoon - Cecchi, Maria Morandi; Pirozzi, M.A. (International journal of computational fluid dynamics, 2002)
The aim of this paper is to investigate the concurrent implementation on Multiple Instruction, Multiple Data (MIMD) distributed memory multiprocessors of a shallow water finite element model built to simulate the tidal motion in the Venice lagoon. A recursive technique is used to partition the meshed computational domain into subdomains of (almost) equal number of elements, a requisite for balance the workload on parallel computers.